Evaluation of Factors Affecting Risk in Real Estate Industry by Relatively Importance Index Method - Jagdishbhai, Parekh Varunkumar (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2015)
Real estate industry is fragmented, very sensitive to the economic cycles & political environment, and has a significantly high rate of business failure. More than 50% of all the real estate businesses have failed within the first five years as risks associated with their startup are not being considered. Business failure is an extremely disruptive force especially in case of construction industry. Previous studies on construction project risk management (PRM) have focused on the project level rather than the enterprise level. Enterprise Risk Management (ERM) is a process affected by an entity’s board of directors, management and other personnel applied in a creating strategies across the enterprise. The objective of this study was to identify and assess the risk associated with the residential real estate business and also to formulate an enterprise risk management model.